The Pension spending in Venezuela. A projection to 2020 (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2020)
Social security is a very relevant issue at present and within it, what concerns pensions, which with in society is a matter of vital importance, especially because the survival of that they have reached the end of their useful life. In this sense, the objective of this research is to determine the expenditure on pensions with respect to the GDP in Venezuela forth period 2015-2020, through a mathematical model, based on forecasts, and thus to determine the sustainability of the pension system. Venezuelan within the framework of the Social Security Law. This research can serve as input forth design of policies related to the issue of social security, related to improvements in the process of allocating pensions by the IVSS, for the benefit of pensioners and provides elements that allowocating the issue of social security in Venezuela within the framework of the theories that support the conformation and success of pension systems. Methodologically, the Monte Carlo model issued to forecast pension be havior with respect to GDP in the aforementioned period, based on the relationship between demographic, institutional and labor factors. It is concluded that the greater the number of people with the age indicated to obtain the benefit, the greater will be the public spending on pensions, in addition to the fac that the labor supply will tend to decrease.
Keywords: social security; pension spending; forecast; GDP; sustainability